2009
DOI: 10.1063/1.3251123
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on effects of hydrogen bonding on the ring stretching modes of pyridine

Abstract: Pyridine generally acts as the proton acceptors in the hydrogen bonding interaction by using its lone pair n(N) or pi-electrons. Some previous research indicated that for the N-type H-bond, the ring breathing mode v(1), the N-para-C stretching mode v(6a) and the meta-CC stretching mode v(8a) of pyridine showed a frequency blueshift but the triangle mode v(12) had no change in frequency. Both electrostatic interaction and charge transfer caused by intermolecular hyperconjugation n(N)-->sigma( *)(HX) have contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The frequency blue shift of the pyridine ring vibration modes caused by formation of the H‐bonding can be interpreted based on two theories. (1) In the N‐type H‐bonds XH ··· N, the intermolecular charge transfer caused by the intermolecular hyperconjugation n (N) → σ*(HX) induces intramolecular charge redistribution, mainly the intramolecular charge transfer from the two antibonding orbitals σ*(meta‐CC) to n (N) 14, 21, 22. This intramolecular charge transfer is just the inverse process of the intramolecular hyperconjugation n (N) → σ*(meta‐CC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency blue shift of the pyridine ring vibration modes caused by formation of the H‐bonding can be interpreted based on two theories. (1) In the N‐type H‐bonds XH ··· N, the intermolecular charge transfer caused by the intermolecular hyperconjugation n (N) → σ*(HX) induces intramolecular charge redistribution, mainly the intramolecular charge transfer from the two antibonding orbitals σ*(meta‐CC) to n (N) 14, 21, 22. This intramolecular charge transfer is just the inverse process of the intramolecular hyperconjugation n (N) → σ*(meta‐CC).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we have studied the N‐type hydrogen bonds of pyridine with proton donors such as CHX 3 (X = F, Cl, Br), HCONH 2 , H 2 O, and CH 3 COOH 21, 22 and discussed the effects of hydrogen bonding on the ring stretching mode of pyridine. We found that the frequency blue shift in the ring stretching mode was related to the sigma meta‐CC bonds of the pyridine ring, whereas the π 66 bond was not involved.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] The HB structures of pyridine-water mixtures in aqueous solutions have been also studied by neutron diffraction, 45 nuclear magnetic resonance (NMR), 46,47 and theoretical methods. [48][49][50][51][52][53] Although local structures of aqueous pyridine solutions are extensively studied by experimental and theoretical methods, the concentration-dependent structural changes of the pyridinewater mixtures have not yet been fully understood. It is because the molecular interactions of pyridine are not easily observed separately from those of solvent water.…”
Section: •1 Concentration Dependence Of Aqueous Pyridine Solutionsmentioning
confidence: 99%
“…(1) In the N-type H-bonds XAHÁÁÁN, the intermolecular charge transfer caused by the intermolecular hyperconjugation n(N) ! r*(HX) induces intramolecular charge redistribution, mainly the intramolecular charge transfer from the two antibonding orbitals r*(meta-CC) to n(N) [14,21,22]. This intramolecular charge transfer is just the inverse process of the intramolecular hyperconjugation n(N) !…”
Section: Influence Of Substituent and H-bonding On The Frequency Of Tmentioning
confidence: 99%
“…In our previous works, we have studied the N-type hydrogen bonds of pyridine with proton donors such as CHX 3 (X ¼ F, Cl, Br), HCONH 2 , H 2 O, and CH 3 COOH [21,22] and discussed the effects of hydrogen bonding on the ring stretching mode of pyridine. We found that the frequency blue shift in the ring stretching mode was related to the sigma meta-CC bonds of the pyridine ring, whereas the p 6 6 bond was not involved.…”
Section: Introductionmentioning
confidence: 99%